RITUAL-RITUAL SEPUTAR HUTAN DAN LADANG SEBAGAI DAYA LENTING MASYARAKAT DAYAK MERATUS DI LOKSADO - P, Rama Tulus (KRITIS, 2019)
There is a Dayak tribe in the Meratus mountains, precisely in the village of Loksado, which is more tribe named as the Meratus Dayak although there are also people who call it the Dayak Bukit. Socially and religiously, this Dayak Meratus community is under heavy pressure from various parties. This pressure was very visible especially among Christian Dayak Meratus people. But in reality, they are able to survive and even develop. That means there is something that causes them to be able to survive and develop. This is then referred to as resilience. By using the method of observation and interviews, the results of the research show that there are several rituals that become their routine agenda, especially those related to farming processions. Balian roles (priests) become central to the rituals that are followed by almost all villagers. Collective awareness that produces collective morality so that it becomes spiritual capital for this community has played a linear role so that they are able to face various challenges in their lives. This becomes very strong when there is divine intervention in it.